Indian Consul-General explores collaboration opportunities with IITA - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
The Consul-General of India to Nigeria, Chandramouli Kumar Kern, visited IITA-CGIAR headquarters in Ibadan from 31 May to 1 June, aiming to strengthen India-Africa collaboration in agricultural research and innovation. Lava Kumar, the IITA Head of Virology and Germplasm Health, moderated the meeting. In his welcome remarks, the IITA Deputy Director General for Research for Development (DDG-R4D), Bernard Vanlauwe, introduced Kern to IITA’s mission, strategy, and core research programs. He also highlighted ongoing collaborations between IITA and Indian research institutions, including: • Development of Fusarium wilt-resistant banana varieties with the National Research Centre for Bananas (NRCB); • Root and tuber crop research with the Central Tuber Crops Research Institute (CTCRI), including capacity building on cassava gene editing and Bambara groundnut breeding; • Genetic resource exchange from IITA genebank and Indian organizations, including the National Bureau of Plant Genetic Resources (NBPGR). India; • Agronomy and soil health initiatives through the Excellence in Agronomy (EiA) program in Odisha, India; and • Biocontrol efforts include successfully introducing predators for papaya mealybug from IITA-Benin and ongoing discussions on scaling Aflasafe in India. The initial follow-up step involves organizing an exchange visit between ICAR experts and IITA and establishing a task force to identify mutual priority areas for Development Partnership grants.